Spiritual entrepreneurship: Beyond self actualization - Hashim, Norashidah; Othman, Norazizah; Abdullah, Syahrina (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
This paper presents the development and validation of a spiritual element of entrepreneurship readiness measure using sequential mixed method approach of item development. Phase one is built content validip into the measure through content analysis of interview data, extant literature review, and content expert item analysis. The development of items for instruments connected the qualitative finding with the second phase of the research which based on quantitative data collection. Phase two established reliability and preliminary construct validity based on the factor analysis of pilot test data. Finally, data was collected to provide further construct validity through cross-validation in a new sample. The resultingfijeen-item spiritual element of entrepreneurship readiness scale demonstrated robust preliminary psychometric properties. The contributions and implications of the present studies, as well as some future research directions, are discussed in the concluding section.